Features of the formation of hybrid humoral immunity to SARS-CoV-2 - L. P. Sizyakina; V. Ya. Zakurskaya (Медицинский вестник Юга России, 2025)
Objective: to assess the dynamics of changes in the levels of specific antibodies in individuals with a history of COVID-19 and those vaccinated with synthetic peptides of SARS-CoV-2. Materials and methods: 40 people who had COVID-19 and immunized with synthetic SARS-CoV-2 peptides were examined. Methods: ELISA diagnostics of specific antibodies to the S and N protein of SARS-CoV-2 and statistical. Results: with COVID-19 in the post-infectious period, the production of S-protein-specific IgG is observed throughout the year from the moment of recovery. Vaccination of recovered individuals with peptide antigens leads to increased synthesis of IgG not only to the S-protein, but also to the N protein of the coronavirus, with a stable tendency towards an increase in antibody content over 3 months of observation. Conclusions: humoral post-infectious immunity is characterized by the predominant production of IgG to the S-protein of SARS-CoV-2, which persist for a year from the moment of recovery, while hybrid immunity, along with the production of antibodies to the S-protein, promotes the predominant synthesis of Ig G to the N protein SARA -CoV-2.